Effect of Sports Participation on Failure in General Life-An Exploratory Study - Muhammad Zafar Iqbal Butt; Muhammad Abdul Jabar Adnan; Qandeel Mughal (The Sky, 2020)
Sports have bit by bit turned into a necessary piece of understudy life. It is a well-acknowledged thought that sports support increments physical wellness and improves wellbeing. The constructive outcomes of physical movement on wellbeing and prosperity have been seen in different researches. The current study has the objective to explore perception of students about effects of sports participation on failures in general life. The nature of the study was quantitative in which data was collected through questionnaire (Close ended) having 20 items, quality of which was categorized on 5-point Likert Type Scale. The population was University students and sample was collected from 200 (n=200) male and female students of University of the Punjab, Lahore using simple random sampling technique. Overall results showed that sports participation may not cause mismanagement in students’ life (Sig. .000), sports participation is not the waste of time (Sig. .000), involvement in university athletics has helped students’ health (Sig. .000), overall career development, socialization, eradication of feelings of loneness (Sig. .000), confidence, mental health, motivation towards success (Sig. .000), physiological and psychological wellbeing (Sig. .000), daily, life style, life barriers management (Sig. .000) in positive way. It is recommended that sports should be the integral part of any academic program or otherwise should be made compulsory along with academic activities in different academic disciplines in all age groups.